Adult education in Greek municipalities during COVID-19 pandemic - Ntafou, Athanasia; Jiménez-Fanjul, Noelia N.; Gutiérrez-Rubio, David (International Journal of Evaluation and Research in Education (IJERE), 2025)
State and local governments’ primary purpose is to provide services to their populations by shaping their social and economic life. Adult education is a good example of a public service that extends deeply into people’s everyday lives. It helps adults increase their social roles as employees, parents, and retiree, gain more fulfilment in their personal lives, and solve personal and community problems. The main research purpose of this paper is to investigate and describe adult education in Greek Municipalities during the COVID-19 pandemic, specifically in the Municipality of Piraeus. For this purpose, the research was conducted using the focus group research method. Two groups participated, the first consisting of four employees of the Center for Lifelong Learning of the Municipality of Piraeus and the second group of four adult learners representing the four courses held. The results of the survey show that the unprecedented situation of COVID-19, particularly affected adult education which had stopped for a while and then many courses were discontinued. The imperative to strengthen digital skills, the uncertainty of continuing education and the change of education as a result of the changing world were also identified.